Comparison of Conventional Keratometry and Total Keratometry in Normal Eyes. (14th April 2020) - Hoshikawa, Rie; Kamiya, Kazutaka; Fujimura, Fusako; Shoji, Nobuyuki
Abstract : Purpose . The relationship between conventional keratometry and total keratometry has not been fully investigated. This study was aimed at conventional keratometry measured with the automated keratometer and total keratometry with the corneal tomographer in ophthalmologically normal subjects. Methods . We enrolled fifty eyes of 50 consecutive subjects (mean   age ± standard   deviation, 34.9 ± 8.0   years ) who have no ophthalmologic diseases, other than refractive errors, with no history of ocular surgery. Conventional keratometry was measured with the automated keratometer. The total keratometry, the true net power (TNP), and the total corneal refractive power (TCRP) were measured with the Scheimpflug camera, and the real power (RP) was measured with anterior segment optical coherence tomography (As-OCT). Anterior keratometries (Km and AvgK) were also measured with the Scheimpflug camera and the As-OCT, respectively. Results . Conventional keratometry was 43.64 ± 1.48  D, which was significantly higher than the TCRP (42.94 ± 1.45  D, p = 0.042 ), the TNP (42.13 ± 1.37  D, p < 0.001 ), and the RP (42.62 ± 1.39  D, p = 0.001, Dunnett's test). We found significant correlations between conventional keratometry and each total corneal power (the TCRP (Pearson's correlation coefficient r = 0.986, p < 0.001 ), the TNP (r = 0.986, p < 0.001 ), the RP (r = 0.987, p < 0.001 ), the Km (r = 0.990, p < 0.001 ), and the AvgK (r = 0.991, p < 0.001 )). The intraclass correlations of conventional keratometry with the TCRP, the TNP, the RP, the Km, and the AvgK were 0.986, 0.983, 0.985, 0.990, and 0.990, respectively. We found no significant differences in the keratometric data measured with the automated keratometer, the Scheimpflug camera, and the As-OCT (ANOVA, p = 0.729 ). Conclusions . Conventional keratometry was significantly larger than total keratometry, by approximately 0.70 to 1.52 D, in ophthalmologically normal subjects. By contrast, there were no significant differences in the keratometric data among the three devices. It is suggested that conventional keratometry overestimates the total corneal power in daily practice.